Définir l’intervention d’André Le Nôtre au château de Meudon : l’exemple d’un réseau hydraulique ambitieux et sophistiqué - Romane Mazzieri (Les Cahiers de l'École du Louvre)
The aim of the study described this article is to define the extent of André Le Nôtre’s intervention at the Château de Meudon and the place of the gardens of Meudon in his work through the analysis of its ambitious, sophisticated hydraulic network. The compilation of an initial inventory of maps and plans from the public archives, dating from the mid-seventeenth century to the mid-nineteenth century, has made it possible to gain a better understanding of the evolution of the gardens of Meudon and, above all, to determine the extent of André Le Nôtre’s involvement. This inventory of maps and plans was also used to determine the characteristics of the hydraulic network of the gardens of Meudon, which is represented and detailed there. Finally, a field survey was carried out to determine the remains of these gardens and to account for the elements that have been preserved and those that have disappeared since the early eighteenth century.